Contemporary use and outcomes of radiation and chemotherapy for unresectable pancreatic cancer. (July 2022) - Moningi, Shalini; Lei, Xiudong; Fang, Penny; Taniguchi, Cullen M.; Holliday, Emma B.; Koay, Eugene J.; Koong, Albert C.; Ludmir, Ethan B.; Minsky, Bruce D.; Das, Prajnan; Giordano, Sharon H.; Smith, Grace L.
Highlights: This study examines 5, 624 patients with unresectable pancreatic cancer. Across "real-world" US practice, overall use of radiation treatment (RT) has declined. Among those receiving RT, stereotactic body radiation treatment (SBRT) increased. Contemporary risks of gastrointestinal complications after SBRT have decreased. Abstract: Background: We assessed radiation treatment (RT) use and complications for unresectable pancreatic cancer in the US, comparing conventionally fractionated (CFRT) and stereotactic body radiation treatment (SBRT) to inform real-world expected outcomes and practice. Material and Methods: We analyzed 5, 624 patients with non-metastatic, unresectable pancreatic cancer (2, 522 older patients age > 65, diagnosed 2006–2013 in Medicare linked data; and 3, 102 younger patients age < 65, diagnosed 2006–2016 in MarketScan data), comparing CFRT vs. SBRT vs. chemotherapy alone. Cochran-Armitage tested temporal trends. Fisher's Exact Test and proportional hazards models compared gastrointestinal (GI) complications. Healthcare payments (Consumer Price Index adjusted to 2015) through 12 months were compared using generalized linear regression models with log link and gamma distribution. Results: RT use declined from 55% to 45% of older patients (2006–2013) and 52% to 47% of younger patients (2006–2016) (Ptrend < 0.001 both). Among RT patients, SBRT use increased to 10% of older patients and 12% of younger patients in the most recent years (Ptrend = 0.04 and < 0.001 respectively). Addition of RT was associated with more frequent GI bleeds, strictures, and fistulas (Δ= +3% to 9% excess events, all P ≤ 0.05). Temporal patterns suggested decreasing complications over time (Ptrend = 0.05 and 0.05 for older and younger patients). Among younger patients, there was no difference in GI complications for SBRT vs. CFRT (P > 0.05, all comparisons). Among older patients, increased complications were seen for SBRT in 1–4 fractions vs. CFRT (P < 0.05), but not SBRT in 5 fractions (P = 0.72). Healthcare payments were greatest for SBRT when compared with CFRT or chemotherapy under US Medicare (P < 0.001) and employer-based insurance (P < 0.001). Conclusion: Real-world treatment has shifted toward more selectivity for RT in unresectable pancreatic cancer. However, SBRT uptake and improving trends in complications profiles represent opportunities to optimize current use and benefit. Findings are applicable to inform future comparative and cost effectiveness models of RT for this disease.